PRODUCTIVE PERFORMANCE OF JERSEY X SAHIWAL COWS IN CHITTOOR DISTRICT OF ANDHRA PRADESH - VARAPRASAD, A. REDDY; RAGHUNANDAN, T.; KUMAR, M. KISHAN; PRAKASH, M. GNANA (Indian Journal of Animal Production and Management, 2017)
ABSTRACTSeason of birth and age at sexual maturity had a non-significant effect on firstlactation milk yield. The overall least-squares mean lactation milk yield was 2154.07 Â± 16.88liters (Lt). Significant effect of batch was found on first lactation milk yield in the presentstudy. Cows belonging to 4th batch recorded significantly (P